THE INFLUENCE OF MOTOR VEHICLE TAX (PKB) BLEACHING AND UNDERSTANDING OF E-SAMSAT ON MOTOR VEHICLE TAXPAYER COMPLIANCE MODERATED BY TAXATION SOCIALIZATION - Fitriyah, Tsamrotul; Munari (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The aim of this study is to assess, scrutinize, and examine the impact of the motor vehicle tax bleaching program and understanding with e-SAMSAT on compliance among motor vehicle taxpayers. Additionally, the research investigates whether the effectiveness of the motor vehicle tax bleaching program and comprehension of e-SAMSAT on motor vehicle taxpayer compliance is moderated by taxation socialization. The study focuses on taxpayers in the Sugio sub-district registered at SAMSAT Lamongan in the year 2023, with a sample size of 100 determined through simple random sampling utilizing the Slovin formula. Data collection involves employing a Likert scale for primary data, and the analysis employs Structural Equations Modeling (SEM) Partial Least Square (PLS) through SmartPLS 4.0 software. The findings reveal that the motor vehicle tax bleaching program does not exert a significant influence. However, understanding e-SAMSAT significantly impacts motor vehicle taxpayer compliance. Furthermore, taxation socialization is identified as a moderating factor, albeit with a weak attenuating effect on the influence of the motor vehicle tax bleaching program and an enhancing effect on the impact of understanding e-SAMSAT on motor vehicle taxpayer compliance. The advice given to Samsat employees from this research is to improve communication and education by conducting outreach to taxpayers regarding the benefits of motor vehicle tax whitening, effective information to ensure taxpayers know about tax whitening and the procedures.